Hopis, tewa, and the American road (University of N.M. Press Albuquerque, New Mexico, 1983)
"The Melville Collection of Indian art, cataloged in this handsome book, was largely assembled in 1927 on the Hopis Mesas. The collection, which belongs to Wesleyan University, the original publisher of this book, also includes Plains, Pima, Pueblo, and Navajo items. The Hopi material comprises traditional pieces intended for local use, innovative items made for sale to tourists, and ceramics that illustrate the complex transition in Hopi pottery from folk craft to :Indian art." In addition to cataloging the collection, the book includes essays on the Tewas and the Hopis, on the Sityatki Revival potters and their wares, on the historical and political context of Indian affairs in the 1920s, on the business of buying and selling Indian art, and on the individuals who made this particular collection." back cover
56497
Keywords: Southwest; Art Private collections; Art hopi; Art tewa; Hopi Indians; Hopi art; Indian art